DIAGNOSIS OF ARTIFICIAL SECONDARY CARIES ON ENAMEL: CORRELATION BETWEEN VISUAL EVALUATION AND SUPERFICIAL MICROHARDNESS - Perito, Mario Alberto Marcondes; Rodrigues, José Augusto (Revista Saúde - UNG-Ser - ISSN 1982-3282, 2009)
This in vitro study evaluated the correlation of artificial secondary caries diagnosis on enamel between visual evaluation and superficial microhardness test. Cavities with standardized diamond burs (1.6mmØ) were prepared on thirty-six enamel blocks obtained from unerupted human third molars and were assigned to 3 groups. Each group was restored with glass-ionomer cement (GI), resin-modified glass-ionomer (RM), or composite resin (CR). Blocks were thermocycled and submitted to a pH challenge to develop artificial caries-like lesions. Lesions were analyzed by visual evaluation using scores and the results were submitted to Kruskal Wallis and Dunn Test. The hardness of the enamel surface surrounding the restored cavity was evaluated using Knoop microhardness test and results were submitted to ANOVA followed by Tukey’s post-hoc test. Afterwards, the correlation between visual and microhardness analyses was verified by Spearman’s rho nonparametric correlation test. Regarding visual analysis, no significant difference was observed between GI and RM groups, which showed less caries development than CR group. The microhardness evaluation showed significant differences among all groups with the least caries development in GI group, followed by RM and CR, respectively. The Spearman’s rho coefficient of correlation demonstrated a significant weak negative correlation between the response variables. The superficial microhardness test was more sensitive to detect artificial secondary caries than visual evaluation.